A vibrating trachea. Issue 3 (1st March 1998) - Doherty, M J; Spence, D P S; Graham, D; Cheetham, B M G; Sun, X Q; Earis, J E
Abstract : A case of relapsing polychondritis presenting as tracheomalacia is reported in which an unusual low pitched sound was heard at the mouth and over the chest wall during expiration. The sound was associated with expiratory airflow limitation and oscillation on the flow trace of approximately 50 Hz. Spectral analysis of the sound showed it to have the characteristics of sounds produced by flutter in flow limited flexible tubes. These observations suggest that the sound was produced by airflow induced flutter in the trachea and main airways and is further evidence in support of the dynamic flutter theory of wheeze production.